High-Precision Control for Switched Reluctance Motor With Current Information - Tao, Zean; Li, Mengqiu; Xu, Mingyi; Liu, Jianlin; Luo, Jianguo (Frontiers in Energy Research, 2022)
Magnetic characteristic of the SRM is able to be monitored directly in the detection commutation instants. However, mutual inductance effect between the adjacent phases is prominent for Switched Reluctance Motor in status of the adjacent phase energized simultaneously. Consequently, the mutual coupling will distort the response current profile of the injection voltage phase, thereby affecting the position estimation precision. In order to acquire a good precise estimation and accommodate this requirement of the SRM drive system, the consideration of modifications for the sensorless scheme is necessary to be taken. This paper presents a unique rotor position estimation approach to eliminate the mutual inductance effect by employing the phase current slope difference method. The sensorless scheme is achieved by setting a low threshold and a high threshold, a series of voltage pulses are injected in idle phase alternately synchronized with the chopping current control. Without a prior knowledge of mutual inductance and any additional position sensor, a precisely estimated rotor position is achieved. A dynamic model of a 12/8 SRM model is established to evaluate its validity and both of simulation results and experimental evaluation indicate that the proposed sensorless control can be accomplished with an adequate precision employed in a variety of applications.